Growth and Yield Response of Sweet Corn (Zea Mays Saccharata Sturt) on Some Green Manure Tithonia Diversifolia and Dose of Em4 - Widodo, Widodo; Sinambela, Anastasia M.L.; Simanihuruk, Bilman W (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
Soil fertility decline as a result of the use of inorganic fertilizers. Tithonia diversifolia is an green manure and EM4 is a mixture of beneficial microorganisms. Application of Tithonia and EM4 on sweet corn is an effort to replace the use of inorganic fertilizers. This study aims to obtain the interaction in application of Tithonia and EM4, to compare at different doses of green manure Tithonia, and to compare on the application of multiple doses of different EM4. Completely Randomized Block Design is used which consist of two factors. The first factor is the dose of Tithonia consisting of: 0 tons ha-1, 10 tons ha-1, 20 tons ha-1 and 30 ton ha-1. The second factor is the dose EM4 comprising: 0 ml L-1, 10 ml L-1 and 20 ml L-1 of water. The results showed that Tithonia diversifolia and EM4 have no effect on the growth and yield of sweet corn. Tithonia diversifolia of 30 tons ha-1 provide the highest plant height and the highest number of leaves and and the largest stem diameter and the highest level of leaf greenish. There is a tendency on the ascending EM4 dosage, will increase the average plant height, leaf number, stem diameter and leaf greenish level. Keywords:Tithonia, EM4, sweet corn.